UMP subject registration system in mainframe environment(zSRS) - Lilan Sollan, Sarveswary (2012)
UMP Subject Registration System in Mainframe Environment (zSRS) is a subject registration system done in the mainframe environment for the system operators to create a batch type input and output system.The system is designed using System-Z as the operating system,to ease the tasks of the system operator to browse for records and view it in a formatted file.It will make use of the logical partition of a mainframe,to run the managerial operations.This report will discuss on the preparation,analysis,development and discussion based on the development cycle of this system. A complete reference and research details have been furnished in this document.This document will be a quick reference to refer on the specification and requirements of the system.